Analisis efektivitas antibiotik levofloxacin dan ceftriaxon pada pasien pneumonia di instalasi rawat inap RSD X Kota Cirebon Tahun 2023 - Efriani, Like; Putra , Teguh Adiyas; Fitriyani, Fifit (Journal of Pharmaceutical and Sciences, 2025)
Pneumonia is inflammation caused by microorganisms such as bacteria, viruses, fungi, and foreign substances that enter the lungs. The therapeutic management of pneumonia is given antibiotics to eliminate the causative bacteria and overall healing. Conceptually, levofloxacin antibiotics are considered better for pneumonia therapy than ceftriaxone. This study aimed to determine the effectiveness of comparing levofloxacin and ceftriaxone antibiotics in pneumonia patients in the inpatient installation of RSD X Cirebon City. Parameters to determine the effectiveness of antibiotics based on body temperature and length of stay (LOS). This study used a retrospective cross-sectional research design. Patient data from medical records were 91 samples that met the inclusion criteria. Data analysis included patient characteristics, antibiotic use, and therapy effectiveness data. Data were tested statistically using Mann-Whitney. The results showed that the comparison of levofloxacin and ceftriaxon had different effectiveness as antibiotic therapy in pneumonia patients hospitalized in RSD X Cirebon City, except based on length of stay.